2011
DOI: 10.1016/j.envexpbot.2010.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of potassium for proper growth and physiological response of Houttuynia cordata Thunb.

Abstract: a b s t r a c tHouttuynia cordata Thunb. is an edible herb with a variety of pharmacological activities, but only limited information is available about its response towards potassium supplementation. Sterile plantlets were cultured in media with different potassium levels, and parameters related to growth, foliar potassium, water and chlorophyll contents, photosynthesis, transpiration, H 2 O 2 contents and antioxidative enzyme activities were determined after a month. Results showed that 1.28 mM potassium was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 55 publications
2
16
0
1
Order By: Relevance
“…In previous reports, antioxidant enzyme (SOD, CAT, peroxidase) activity was increased in K‐deficient bean ( Phaseolus vulgaris L.) leaves and chameleon plant ( Houttuynia cordata Thunb. ), being in accordance with the increased SOD activity found in K125 compared with K375 treatment (Fig. C).…”
Section: Discussionsupporting
confidence: 89%
“…In previous reports, antioxidant enzyme (SOD, CAT, peroxidase) activity was increased in K‐deficient bean ( Phaseolus vulgaris L.) leaves and chameleon plant ( Houttuynia cordata Thunb. ), being in accordance with the increased SOD activity found in K125 compared with K375 treatment (Fig. C).…”
Section: Discussionsupporting
confidence: 89%
“…Shin et al (2005) (Hafsi et al, 2014). Although the increased K levels resulted in higher contents of leaf potassium as compared to lower K levels, the higher leaf potassium did not improve the plant biomass, being in accordance with previous studies (Xu et al, 2011). Potassium interacts with almost all essential elements.…”
Section: Discussionsupporting
confidence: 78%
“…H 2 O 2 can be removed through the ascorbate-glutathione cycle AsA-GSH whereas the APX and the SOD are the key enzymes in this cycle (Pasternak et al, 2005). Antioxidant enzymes (SOD, CAT, peroxidase) activity increased in K-deficient bean leaves (Cakmak, 2005) and Houttuynia cordata (Xu et al, 2011). Results of the present study showed that 325 mg L -1 of K application decreased the MDA content compared with the 275 mg L -1 of K, maybe by elimination of free radicals (Sharma et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Potassium starvation and high potassium conditions cause oxidative stress due to the formation of reactive oxygen species (ROS; e.g., O 2 •− and H 2 O 2 ) [43], [59], [60], [61]. To protect themselves against the injurious effects of ROS, plants have evolved complex antioxidant system which includes enzymatic antioxidants and non-enzymatic antioxidants [62].…”
Section: Discussionmentioning
confidence: 99%